Polityka rolna Wspólnoty w Jednolitym Rynku Europejskim: [Community Agricultural Policy in the Single European Market] (Studia Prawnicze / The Legal Studies, 1993)
W odniesieniu do wspólnej polityki rolnej, zgodnie z art. 253 Traktatu ustanawiającego Wspólnotę Europejską, określenie podstawy prawnej wymaga od wspólnotowego legislatora wyznaczenia zakresu owej polityki, zakresu w jakim rolnictwo traktowane jest jako specjalny sektor oraz stosunków między wspólną polityką rolną a Jednolitym Rynkiem Europejskim. With regard to the Common Agricultural Policy, in accordance with Article 253 of the Treaty establishing the European Community, the definition of the legal basis requires the Community legislator to define the scope of this policy, the extent to which agriculture is treated as a special sector and the relationship between the Common Agricultural Policy and the Single European Market.